A new species of the genus Peristylus (Orchidaceae) from southern Thailand - Kurzweil, Hubert; Tripetch, Petch (Thai Forest Bulletin (Botany), 2015)
A new species of the genus Peristylus Blume is described from Phangnga Province in Peninsular Thailand. On account of its small size, slender habit, lip shape and spur shape the species is very distinct from any other species found in Thailand and neighbouring countries. A morphological description, short notes on the distribution, ecology, phenology and conservation as well as illustrations of the species are provided.